2018
DOI: 10.17159/2221-4070/2018/v7i2a5
|View full text |Cite
|
Sign up to set email alerts
|

Engaging critical emancipatory research as an alternative to mitigate school violence in South Africa

Abstract: In this theoretical paper, we contribute to ongoing narratives that attempt to mitigate and curb school violence. We do this by critiquing school relations through the lens of critical emancipatory research. Critical emancipatory research has the impetus to map skewed relations that exacerbate school violence in South African schools. In order to achieve our aim, we highlight various principles of critical emancipatory research that position the theory so that it relates to rebuilding school safety to achieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 16 publications
(18 reference statements)
0
21
0
Order By: Relevance
“…Thematic analysis (TA) was used to analyze the generated data (Braun & Clarke, 2006). Reflexive thematic analysis theory as used in this study was found to be appropriate to analyzing qualitative data to answer broad or narrow research questions about people's experiences, views and perceptions, and representations of a given phenomena (Dube & Hlalele, 2018). This process was originally developed for psychology research by Virginia Braun and Victoria Clarke (Msimanga, 2017;Makoelle, 2013;Adebola, Tsotetsi & Omodan, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thematic analysis (TA) was used to analyze the generated data (Braun & Clarke, 2006). Reflexive thematic analysis theory as used in this study was found to be appropriate to analyzing qualitative data to answer broad or narrow research questions about people's experiences, views and perceptions, and representations of a given phenomena (Dube & Hlalele, 2018). This process was originally developed for psychology research by Virginia Braun and Victoria Clarke (Msimanga, 2017;Makoelle, 2013;Adebola, Tsotetsi & Omodan, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…All the relevant stakeholders were engaged, and operated under equal power relations (Hlalele, 2018) and, therefore, owned the process of research, from identifying the research topic to collecting and analyzing data (Mahlomaholo, 2014). The aim of working together with the participants as a team was to create a space for the participants to be empowered as CER advocates (Dube & Hlalele, 2018;Mashego, 2012). Thus, CER enabled me to listen to the participants and work with them to determine the pathways we used to mitigate the challenges of learners' academic performance.…”
Section: Critical Emancipatory Researchmentioning
confidence: 99%
See 3 more Smart Citations